Christian Citizens : Reading the Bible in Black and White in the Postemancipation South - Jemison, Elizabeth L. (Book collections on Project MUSE., 2020)
"With emancipation, a long battle for equal citizenship began. Bringing together the histories of religion, race, and the South, Elizabeth L. Jemison shows how southerners, black and white, drew on biblical narratives as the basis for very different political imaginaries during and after Reconstruction. Focusing on everyday Protestants in the Mississippi River Valley, Jemison scours their biblical thinking and religious attitudes toward race. She argues that the evangelical groups that dominated this portion of the South shaped contesting visions of black and white rights"--